32.8k views
4 votes
Second derivative of x^½ + y^½ = a^½

User Tltjr
by
5.4k points

1 Answer

5 votes

Answer:


\displaystyle y'' = \frac{√(x) + √(y)}{2x^\big{(3)/(2)}}

General Formulas and Concepts:

Calculus

Differentiation

  • Derivatives
  • Derivative Notation

Derivative Property [Multiplied Constant]:
\displaystyle (d)/(dx) [cf(x)] = c \cdot f'(x)

Derivative Property [Addition/Subtraction]:
\displaystyle (d)/(dx)[f(x) + g(x)] = (d)/(dx)[f(x)] + (d)/(dx)[g(x)]

Basic Power Rule:

  1. f(x) = cxⁿ
  2. f’(x) = c·nxⁿ⁻¹

Derivative Rule [Quotient Rule]:
\displaystyle (d)/(dx) [(f(x))/(g(x)) ]=(g(x)f'(x)-g'(x)f(x))/(g^2(x))

Derivative Rule [Chain Rule]:
\displaystyle (d)/(dx)[f(g(x))] =f'(g(x)) \cdot g'(x)

Implicit Differentiation

Explanation:

*Note:

Allow a to be defined as an arbitrary constant.

Step 1: Define


\displaystyle x^\big{(1)/(2)} + y^\big{(1)/(2)} = a^\big{(1)/(2)}

Step 2: Differentiate

  1. Basic Power Rule [Addition/Subtraction, Chain Rule]:
    \displaystyle (1)/(2√(x)) + (y')/(2√(y)) = 0
  2. Isolate y' term:
    \displaystyle (y')/(2√(y)) = -(1)/(2√(x))
  3. Isolate y':
    \displaystyle y' = -(√(y))/(√(x))
  4. Derivative Rule [Quotient Rule]:
    \displaystyle y'' = -((√(y))'(√(x)) - √(y)(√(x))')/((√(x))^2)
  5. Basic Power Rule [Derivative Rule - Chain Rule]:
    \displaystyle y'' = -((y'√(x))/(2√(y)) - (√(y))/(2√(x)))/((√(x))^2)
  6. Simplify:
    \displaystyle y'' = -((y'√(x))/(2√(y)) - (√(y))/(2√(x)))/(x)
  7. Rewrite:
    \displaystyle y'' = \frac{-(y'x - y)}{2x^\big{(3)/(2)}√(y)}
  8. Substitute in y':
    \displaystyle y'' = \frac{-(-(√(y))/(√(x))x - y)}{2x^\big{(3)/(2)}√(y)}
  9. Simplify:
    \displaystyle y'' = \frac{√(x) + √(y)}{2x^\big{(3)/(2)}}

Topic: AP Calculus AB/BC (Calculus I/I + II)

Unit: Differentiation

User Dawid Sajdak
by
5.2k points